PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. WIJAYA PALEMBANG - Telly Pauline Ulviana Siwi (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2019)
This research aims to analyze the effect of compensation on employee job satisfaction on PT.Wijaya Palembang. The compensation given by the company intended to motivate employees to be able to increase the productivity of the company. Namely the basic salary allowances, transport allowance, other allowances other form of medical benefits, housing allowances, and family allowances, as well as incentives, bonuses and overtime. In this study, the authors used a qualitative and quantitative approach. Data collection techniques using interview, observation,documentation and literature. The data used are primary data and secondary data. Primary data sourced from the first party without certain media, such as questionnaries and interview list, while secondary data in the form of information organization, task and activities undertaken by the company, the data analysis technique used is simple linear regression and testing of the coefficient of determination using statistical program the results of this study indicate that there are significant compensation to employee satisfaction at PT. Wijaya Palembang, r square value of 0,227 means that these two variables have contributed as much as 22,7% on employee job satisfaction PT. Wijaya Palembang there are significant positive and significant correlation betweem compensation job satisfaction partially namely 3,875 t count > t table 1,675 which means H 0 rejected and Hi accepted, this proves that the compensation and significant effect on satisfaction.